Pengaruh Gerak Pemakanan (Feeding) Terhadap Hasil Kekasaran Permukaan Baja Karbon S45C Pada Proses Mesin CNC Turning SKT 160A - Febrianton, Adi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
CNC machine is a machine tool whose entire operation is controlled using a computer by inputting N and G codes. There are 2 types of programming for CNC lathes, namely incremental (the starting point of the program can change or the program endpoint becomes the beginning point of the next program), absolute (the starting point becomes the fixed reference point of the program. The study aimed to determine the low surface roughness value of S45C carbon steel with feeding motion variations of 0.15 mm, 0.25 mm, and 0.35 mm with a cutting depth of 0.4 mm and a constant spindle rotation speed. The insert used is branded iscar with a radius of 0.8 mm.. The lowest roughness value at feeding motion of 0.15 mm belongs to the roughness class, namely N7. The intermediate roughness value at feeding motion of 0.25 mm belongs to the roughness class N7. While the highest roughness value in feeding motion (feeding) 0.35 mm is included in the roughness class, namely N8. The average value results are obtained from the testing process using a roughness test tool (stylus).. The effect of feeding motion on the results of the surface roughness of S45C carbon steel in the CNC process is that the smaller the feeding value, the lower the roughness value produced, while the greater the feeding value, the higher the roughness value produced.